Comprehensive analysis of the coated component from a FORD engine - Hren, Iryna; Michna, Štefan; Novotný, Jan; Michnová, Lenka (Manufacturing Technology Journal, 2021)
The article is devoted to a comprehensive analysis of the coating of a component from the Ford Fo-cus 1.0 l EcoBoost engine. It is one of a pair of materially identical aluminum gears connected by a drive pulley and a drive. Aluminum gear components are surface treated with a mixture of metal powders using PVD technology, where the goal of the coating is to increase the hardness, abrasion resistance and heat of the base material. The chemical composition of the basic material of the gea-red aluminum drive wheel of the FORD engine proves that it is a component made by thermofor-ming and corresponds to the alloy EN AW 6061 (AlMg1SiCu) according to the standard ČSN EN 573 1-3. The microstructure of the base material component exhibits fine intermetallic phases evenly dis-tributed throughout the cross-section of the base base material, without the occurrence of larger inc-lusions and/or porosity. The cross-sectional microstructure in the area of the coating demonstrates that the component has a continuous uniform surface layer of the coating formed without a defect and does not have a diffuse bond with the base material. The measurement of the coating thickness of the component shows a continuous surface layer formed by powder metallography, which ranges from 70.1 µm to 143.9 µm. The surface EDS of the surface proves that it consists of deposited tungsten carbides produced by powder metallography and the bonding material is cobalt. Area EDS analysis of the surface coating identified morphologically two distinct areas of dark and light, where tungsten carbides and cobalt are based, and only the tungsten carbide and cobalt carbide contents change. The oxygen and carbon content also changes in the dark and light areas.
Keywords: FORD engine; component; coating; base material; scanning electron microscopy; EDS analysis; metallo-graphic analysis; chemical analysis.